2019
DOI: 10.4103/ijt.ijt_6_19
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life assessment in patients with androgenetic alopecia

Abstract: Background: Male-pattern alopecia (MPA) or androgenetic alopecia (AGA) is a commonly encountered dermatological condition present in males and is less common among females. Although AGA is a physiological condition, its impact on person's self-esteem is so great that it cannot be ignored. It has a significant affect over a variety of physiological and social aspects of one's life and even on the individual's overall quality of life (QOL). Aims and Objectives: The aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 20 publications
4
66
1
2
Order By: Relevance
“…Many studies demonstrated that patients of younger age had a decreased QoL. 1,5,[8][9][10]22 In contrary to our results, Kranz found that psychological distress due to hair loss depended neither on the age of participants nor on the stage of balding. 28 In accordance, Al Mubki et al demonstrated that QoL was not affected by the patient's age in their study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Many studies demonstrated that patients of younger age had a decreased QoL. 1,5,[8][9][10]22 In contrary to our results, Kranz found that psychological distress due to hair loss depended neither on the age of participants nor on the stage of balding. 28 In accordance, Al Mubki et al demonstrated that QoL was not affected by the patient's age in their study.…”
Section: Discussioncontrasting
confidence: 99%
“…In accordance with our results, multiple researchers concluded that the longer the duration of AGA is; the more is the progression of hair loss and the more intolerance to alopecia is. 1,5,8,22 On the contrary, Mubki et al reported that QoL was not affected by the duration of the disease. A possible explanation for that is patients may gradually adapt to their chronic disease, such as AGA, and as time passes, their QoL gradually improves.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Additional Supporting Information may be found online in Supporting Information: Letters to the Editors focused on specific diseases, for example, androgenetic alopecia. 4,5 This prospective cross-sectional study was conducted at a tertiary dermatological centre. The centre sees an average of 1560 new consultations for hair disorders annually, representing 4.9% of total new cases seen.…”
Section: Supporting Informationmentioning
confidence: 99%
“…By embracing a diverse study population including those with mild and undiagnosed hair loss, we found a lower impact on QoL compared with other studies. 1,2,4,6 The strong racial component with Indians and South Asians (e.g. Pakistani, Sri Lankans) having worse QoL compared with Chinese and Malays highlights the cultural variation, with certain races placing more importance in the fullness of hair.…”
Section: Supporting Informationmentioning
confidence: 99%